2020
DOI: 10.1049/el.2019.1581
|View full text |Cite
|
Sign up to set email alerts
|

Design and test of a broadband rectangular waveguide TE 10 –TE 20 mode converter

Abstract: A broadband rectangular waveguide TE 10-TE 20 mode converter with high mode purity and conversion efficiency is designed, fabricated and measured in this Letter. Based on the broadband characteristic of ridged twist waveguide and its characteristic of polarisation direction torsion of electromagnetic wave, this mode converter achieves broadband and high-efficiency TE 10-TE 20 mode conversion. Simulation results reveal that the return loss of the proposed mode converter is >20 dB and insertion loss is <0.04 dB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Table 1 provides comparisons with previous works. The converters in [3,4,6,9,11] don't possess coplanar and codirectional configuration. The converters in [5,8,12] suffer from difficult fabrication process because of bend waveguides or dielectric rods.…”
Section: Simulation Results Of the Mode Convertermentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides comparisons with previous works. The converters in [3,4,6,9,11] don't possess coplanar and codirectional configuration. The converters in [5,8,12] suffer from difficult fabrication process because of bend waveguides or dielectric rods.…”
Section: Simulation Results Of the Mode Convertermentioning
confidence: 99%
“…Thus, many kinds of mode converters are required to realize the excitation and extraction of higher order modes. Among these, rectangular TE 10 to TE 20 mode converter is basic and has been utilized as an intermediate employed in various applications, such as TE 01 and TE 21 launchers [1][2][3][4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to work with TE20 mode propagation and to make measurements, a TE10 to TE20 mode converter needed to be developed. Waveguide mode converters have already been developed for many microwave applications [17,18]. The TE10 to TE20 mode converter in the present study was developed and designed based on the work reported in [19], considering the central frequency to be 15 GHz.…”
Section: Rectangular Waveguide Te10 To Te20 Mode Convertermentioning
confidence: 99%